Knowledge level of dentists and dental specialists on the use of dental portable x-ray - Faatihah, Amaliya Ummul; Rahasdini, Puri; Ilmayah, Ilmayah; Kurniawan, Septian Bagus; Andaria, Rully Zaidan; Epsilawati, Lusi; Sam, Belly; Pramanik, Farina (Ikatan Radiologi Kedokteran Gigi Indonesia, 2025)
Objectives: Portable X-ray is one of the mobile radiography equipment. It is made with special technological characteristics. It is designed for diagnostic purposes in areas that are far from health facilities. It is considered easy to use and also beneficial. This study aimed to assess the level of knowledge of general and dental specialists on the use, protection, and benefits of dental portable X-rays. Materials and Methods: The study used a descriptive-analytic method design with a survey technique through a closed questionnaire distributed online to respondents in September 2024. Results: This study netted 169 respondents with the results. For question category 1, 43.7% understood, and categories 2 and 3 were very well understood. Conclusion: The understanding of portable X-ray is in the moderate category, its utilization is classified as very good, and the goal, understanding, and knowledge of radiation protection is good.